Fundamentals of Ethnic Hair : The Dermatologist's Perspective - Aguh, Crystal; Okoye, Ginette A. (Springer International Publishing : Imprint: Springer, 2017)
Written to address the growing trend of hair loss in ethnic populations, The Fundamentals of Ethnic Hair: A Dermatologist's Perspective elucidates the science of curly hair, demystifies prevailing hair styling trends, and presents practical advice for minimizing the harmful effects of these hair styling practices. Written from a dermatologist's perspective, this textbook seamlessly blends science and practical management. Chapters include physical and chemical properties of the hair, thermal and chemical straightening, extensions, razor bumps and special cultural considerations.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books